REVISION SISTEMATICA DEL GENERO ACOUSMATICUS BUTLER, 1882 (LEPIDOPTERA:COSSIDAE) - Gentili, Patricia (Acta Entomológica Chilena, 2022)
The genus Acousmaticus Butler, 1882 comprises two species endemic to Central Chile. The genus and its type species are redescribed, and a new species is described. Acousmaticus, orieinally described in the Psychidae, is currently placed in the Cossidae (Lepidoptera.’Ditrysia). Its systeinatic position is discussed, and is tentaiivcly placed in the Hypoptinae (Cossidae) until further evidence (e.g. female genitalia and inmaturc stages) is available.